Is it wrong to try to pick up girls in a dungeon? : four panel comic : days of goddess - Omori, Fujino (Yen Press, 2018)
For the gods and goddesses who give their followers Blessings to dive into the Dungeon, there's nothing they won't do for the sake of their familia. But have you ever wondered how they spend their days while their brave adventurers are busy fighting down below? Get a rare glimpse into the rare and just a tiny bit slapstick daily lives of the deities of Orario, 4-koma style!